Modeling electron competition among nitrogen oxides reduction and N2O accumulation in denitrification - Pan, Yuting; Ni, Bing-Jie; Yuan, Zhiguo (Environmental science & technology, 2013)
Competition for electrons among different steps of denitrification has previously been shown to occur, and to play an important role in the accumulation and emission of N2O in wastewater treatment. However, this electron competition is not recognized in the current denitrification models, limiting their ability to predict N2O accumulation during denitrification. In this work, a new denitrification model is developed for wastewater treatment processes. It describes electron competition among the four steps of denitrification, through modeling the carbon oxidation and nitrogen reduction processes separately, in contrast to the existing models that directly couple these two types of processes. Electron carriers are introduced to link carbon oxidation, which donates electrons to carriers, and nitrogen oxides reduction, which receives electrons from these carriers. The relative ability of each denitrification step to compete for electrons is modeled through the use of different affinity constants with reduced carriers. Model calibration and validation results demonstrate that the developed model is able to reasonably describe the nitrate, nitrite, and N2O reduction rates of a methanol-utilizing denitrifying culture under various carbon and nitrogen oxides supplying conditions. The model proposed, while subject to further validation, is expected to enhance our ability to predict N2O accumulation in denitrification.